2015
DOI: 10.1128/aac.00530-15
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Effect of Ceftaroline-Avibactam on the Normal Human Intestinal Microbiota

Abstract: Ceftaroline-avibactam is a new combination of the antibiotic ceftaroline with a novel non-␤-lactam ␤-lactamase inhibitor, avibactam. The purpose of the present study was to investigate the effect of ceftaroline-avibactam on the human intestinal microbiota. Fourteen healthy volunteers received ceftaroline-avibactam (600 mg ceftaroline fosamil and 600 mg avibactam) intravenously over 2 h every 8 h on days 1 to 6 and as a single dose on day 7. Fecal samples were collected on day ؊1 (within 24 h of the first infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The results also showed that Bacteroides abundance was not significantly altered by cephalosporin. It supports previous findings investigating the effect of cephalosporins on the intestinal microbiota (Burdet et al 2019;Rashid et al 2015). Apart from a decrease in the abundance of several genera, there was an increase in Christensenella, Rothia, Abiotrophia, Acinetobacter, Anaerotruncus, Holdemania, and Turicibacter.…”
Section: Discussionsupporting
confidence: 91%
“…The results also showed that Bacteroides abundance was not significantly altered by cephalosporin. It supports previous findings investigating the effect of cephalosporins on the intestinal microbiota (Burdet et al 2019;Rashid et al 2015). Apart from a decrease in the abundance of several genera, there was an increase in Christensenella, Rothia, Abiotrophia, Acinetobacter, Anaerotruncus, Holdemania, and Turicibacter.…”
Section: Discussionsupporting
confidence: 91%
“…A toxigenic C. difficile strain was reported in one patient, but this was not associated with adverse events. 57 …”
Section: Are All Cephalosporins the Same With Regard To CDI Risk?mentioning
confidence: 99%
“…While this has been demonstrated using murine models (81), monitoring human C. albicans intestinal colonization levels is more problematic. However, more recent clinical studies examining fecal loads have demonstrated increased Candida levels with antibotic treatment (101). Overgrowth may facilitate localized mucosal infection and/or generalized GI tract disturbances, but the validity of GI candidiasis via overgrowth as a clinical entity is controversial (102,103).…”
Section: Non-cd4mentioning
confidence: 99%